Produktivitas Perikanan Tangkap Jaring Purse Seine - Herna Octivia Damayanti (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2020)
ENGLISHPurse Seine net was one of the fishing gear with dominant catch results in Pati Regency. The catch results affected the business productivity of the purse seine net. The purpose of this research was to analyze the business productivity of the Purse Seine net fisheries in Pati Regency. The research was a descriptive study with a quantitative approach. The research was conducted in November 2018 until April 2019 with locations in Bajomulyo and Bendar Village, Juwana District, Pati Regency. The research sampling consisted of 56 samples. Data analysis with partial productivity calculation including productivity per trip, productivity per PK, productivity per crew and productivity per GT. The results showed that (1) the productivity of purse seine boat has exceeded the legalized regulations (1.30 tons/GT), (2) productivity per trip / per PK / per GT showed that the proxy of productivity (per trip, per PK, per GT) was not linearly proportional to the number of trip / PK engine / GT boat, (3) productivity per crew showed how much productivity per crew produced was not linearly proportional to the number of crews departed. INDONESIAJaring Purse Seine merupakan salah satu alat tangkap dengan hasil tangkapan dominan di Kabupaten Pati. Hasil tangkapan berpengaruh terhadap produktivitas usaha jaring Purse Seine. Tujuan penelitian adalah untuk menganalisis produktivitas usaha perikanan jaring Purse Seine di Kabupaten Pati. Penelitian merupakan penelitian deskriptif dengan pendekatan kuantitatif. Waktu penelitian bulan November 2018 sampai dengan April 2019 dengan lokasi di Desa Bajomulyo dan Desa Bendar Kecamatan Juwana Kabupaten Pati. Sampel penelitian berjumlah 56 sampel. Analisis data dengan perhitungan produktivitas parsial yaitu produktivitas per trip, produktivitas per PK, produktivitas per ABK dan produktivitas per GT. Hasil penelitian menunjukkan bahwa (1) produktivitas kapal purse seine telah melebihi peraturan yang ditetapkan (1,30 ton/GT), (2) produktivitas per trip/per PK/per GT menunjukkan bahwa besar kecilnya produktivitas (per trip, per PK, per GT) tidak berbanding lurus dengan banyak sedikitnya jumlah trip/PK mesin/GT kapal, (3) produktivitas per ABK menunjukkan banyak sedikitnya produktivitas per ABK yang dihasilkan tidak berbanding lurus dengan banyak sedikitnya ABK yang diberangkatkan.